Gender Dynamics in Urban Space Usage: A Case Study of Tebessa’s Historic City Centre, Algeria - Soufiane Fezzai; Lambros T. Doulos; Abdelhakim Mesloub (Urban Science)
This study examines the gender dynamics in urban space usage within the historic city center of Tebessa, Algeria, exploring how cultural factors and street networks influence gender-specific pedestrian behavior and land use patterns. Using a multidisciplinary approach combining space syntax techniques, GIS analysis, and behavioral data collection, we analyzed the relationships between street networks, land use attractors, and gender-differentiated pedestrian flows. Key findings reveal significant differences in spatial navigation patterns between men and women, influenced by cultural norms and gender-specific land use distribution. Women’s movement is more constrained and focused on specific attractors, while men navigate the entire urban system more freely. The study also highlights the impact of “edge effects”, where extramural attractors strongly influence intramural gender movement, particularly for women. These gender-specific patterns often override street network influences predicted by traditional space syntax theories. Our research contributes to the understanding of sustainable urban development in culturally rich contexts by demonstrating the need for gender-inclusive planning that considers local cultural practices. The findings have important implications for urban planners and policymakers working to create more equitable and functional historic city centers while preserving cultural heritage and addressing gender-specific needs.